The Effects of Volcanic Ash from Puyehue-Caulle Range Eruption on the Survival of Dichroplus vittigerum - Fernandez Arhex, Valeria Cristina (2013)
The aim of this work was to evaluate the toxicity of volcanic ash from the volcanic complex Puyehue-Caulle Range on the grasshopper, Dichroplus vittigerum, and compare the results with the effect of diatomaceous earth, an organic pesticide. To test this, we carried out 2 experiments: (i) an acute toxicity test, which consisted of exposing adults of D. vittigerum differentially to volcanic ash and diatomaceous earth, and (ii) a study to determine the survival time of the adult stage by separately exposing the insects to diatomaceous earth and volcanic ash, and by simulating with fans the wind gusts that occur naturally in the area of influence of the volcano. The laboratory data showed that constant exposure to volcanic ash and diatomaceous earth induces mortality in adult grasshoppers. Interestingly, the toxicities of the 2 products were very similar. These results suggest that the onset of the volcanic eruption with the consequent suspension of the pyroclastic material in the air may have had a negative impact on D. vittigerum populations through the mortality of individual adults. In summary, volcanic ash has an insecticidal effect similar to that of diatomaceous earth.